ANXA1 directs Schwann cells proliferation and migration to accelerate nerve regeneration through the FPR2/AMPK pathway. Issue 10 (27th August 2020) - Xia, Wenzheng; Zhu, Jin; Wang, Xueyi; Tang, Yinda; Zhou, Ping; Hou, Meng; Li, Shiting
Abstract: Many factors are involved in the process of nerve regeneration. Understanding the mechanisms regarding how these factors promote an efficient remyelination is crucial to deciphering the molecular and cellular processes required to promote nerve repair. Schwann cells (SCs) play a central role in the process of peripheral nerve repair/regeneration. Using a model of facial nerve crush injury and repair, we identified Annexin A1 (ANXA1) as the extracellular trigger of SC proliferation and migration. ANXA1 activated formyl peptide receptor 2 (FPR2) receptors and the downstream adenosine 5′‐monophosphate (AMP)‐activated protein kinase (AMPK) signaling cascade, leading to SC proliferation and migration in vitro. SCs lacking FPR2 or AMPK displayed a defect in proliferation and migration. After facial nerve injury (FNI), ANXA1 promoted the proliferation of SCs and nerve regeneration in vivo. Collectively, these data identified the ANXA1/FPR2/AMPK axis as an important pathway in SC proliferation and migration. ANXA1‐induced remyelination and SC proliferation promotes FNI regeneration.